Identification and characterization of novel B-cell epitopes on the VP2 protein of bluetongue virus serotype 1 - Yuqing Song; Fanhua Meng; Yanling Bao; Wanbin Hu; Zhancheng Tian; Guiquan Guan; Jijun He; Youjun Shang; Hong Yin; Junzheng Du (Veterinary Microbiology, 2026)

Effects of long-term vegetation restoration on soil aggregate and aggregate-associated nutrient stoichiometry of desertified grassland on the eastern Qinghai–Tibet Plateau - Zhong Du; Rui Zhou; Yan Chen; Enran Zhan; Youjun Chen; Huan Zheng; Dongzhou Deng; Li He; Dechao Chen; Huijun Gao; Yiqun Liu (Agriculture, Ecosystems & Environment, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Core-shell hydrogel microspheres with sequential delivery of cerium oxide nanoparticles and spinal white matter extracellular matrix for improved functional recovery in spinal cord injury - Yixiang Ai; Chunping Hu; Yifan Wang; Youjun Liu; Renfeng Liu; Hailiang Xu; Hui Li; Yuqi Zhao; Yuhao Wang; Ruojie Ning; Cheng Ju; Weidong Wu; et al. (Chemical Engineering Journal, 2025)

Organic-inorganic geochemistry and paleontology reveal the Paleocene paleoecology and source rock development in the Lishui-Jiaojiang Sag, East China Sea Shelf Basin - Jiahao He; Dujie Hou; Youjun Tang; Ting Wang; Jun Qin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effect of three unsaturated fatty acids on the protein oxidation and structure of myofibrillar proteins from rainbow trout (Oncorhynchus mykiss) - Youjun Wang; Yangmeijin Zhao; Yuxuan He; Chengxiang Ao; Yusheng Jiang; Yuanyong Tian; Hui Zhao; Hang Lu (Food Chemistry, 2024)

Glutathione S-transferase directly metabolizes imidacloprid in the whitefly, Bemisia tabaci - Rong Zhang; Jing Yang; Jinyu Hu; Fengbo Yang; Jinjin Liang; Hu Xue; Xuegao Wei; Buli Fu; Mingjiao Huang; He Du; Chao Wang; Qi Su; et al. (Pesticide Biochemistry and Physiology, 2024)

Exploring plant characteristics for constructing a pre-border weed risk assessment for China - Fang Wang; Jing Huang; Ning Zhang; Youjun Li; Shanyong He; Junbao Wen; Liping Yin; Yibing Liang (Biological Invasions, 2024)

Curcumin-activated Olfactory Ensheathing Cells Improve Functional Recovery After Spinal Cord Injury by Modulating Microglia Polarization Through APOE/TREM2/NF-κB Signaling Pathway - Chao Jiang; Zhe Chen; Xiaohui Wang; Yongyuan Zhang; Xinyu Guo; Hong Fan; Dageng Huang; Yuqing He; Xiangwen Tang; Yixiang Ai; Youjun Liu; Hao Yang; et al. (Journal of Neuroimmune Pharmacology, 2023)
Transplantation of curcumin-activated olfactory ensheathing cells (aOECs) improved functional recovery in spinal cord injury (SCI) rats. Nevertheless, little is known considering the underlying mechanisms. At the present study, we investigated the promotion of regeneration and functional recovery after transplantation of aOECs into rats with SCI and the possible underlying molecular mechanisms. Primary OECs were prepared from the olfactory bulb of rats, followed by treatment with 1µM CCM at 7–10 days of culture, resulting in cell activation. Concomitantly, rat SCI model was developed to evaluate the effects of transplantation of aOECs in vivo. Subsequently, microglia were isolated, stimulated with 100 ng/mL lipopolysaccharide (LPS) for 24 h to polarize to M1 phenotype and treated by aOECs conditional medium (aOECs-CM) and OECs conditional medium (OECs-CM), respectively. Changes in the expression of pro-inflammatory and anti-inflammatory phenotypic markers expression were detected using western blotting and immunofluorescence staining, respectively. Finally, a series of molecular biological experiments including knock-down of triggering receptor expressed on myeloid cells 2 (TREM2) and analysis of the level of apolipoprotein E (APOE) expression were performed to investigate the underlying mechanism of involvement of CCM-activated OECs in modulating microglia polarization, leading to neural regeneration and function recovery. CCM-activated OECs effectively attenuated deleterious inflammation by regulating microglia polarization from the pro-inflammatory (M1) to anti-inflammatory (M2) phenotype in SCI rats and facilitated functional recovery after SCI. In addition, microglial polarization to M2 elicited by aOECs-CM in LPS-induced microglia was effectively reversed when TREM2 expression was downregulated. More importantly, the in vitro findings indicated that aOECs-CM potentiating LPS-induced microglial polarization to M2 was partially mediated by the TREM2/nuclear factor kappa beta (NF-κB) signaling pathway. Besides, the expression of APOE significantly increased in CCM-treated OECs. CCM-activated OECs could alleviate inflammation after SCI by switching microglial polarization from M1 to M2, which was likely mediated by the APOE/TREM2/NF-κB pathway, and thus ameliorated neurological function. Therefore, the present finding is of paramount significance to enrich the understanding of underlying molecular mechanism of aOECs-based therapy and provide a novel therapeutic approach for treatment of SCI.

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Correction to: The whole genomic analysis of the Orf virus strains ORFV‑SC and ORFV‑SC1 from the Sichuan province and their weak pathological response in rabbits - Guoyu Du; Jinyan Wu; Cheng Zhang; Xiaoan Cao; Lingxia Li; Jijun He; Yong Zhang; Youjun Shang (Functional & Integrative Genomics, 2023)

The whole genomic analysis of the Orf virus strains ORFV-SC and ORFV-SC1 from the Sichuan province and their weak pathological response in rabbits - Guoyu Du; Jinyan Wu; Cheng Zhang; Xiaoan Cao; Lingxia Li; Jijun He; Yong Zhang; Youjun Shang (Functional & Integrative Genomics, 2023)
The Orf virus (ORFV) is a member of the Parapoxvirus genus of the Poxviridae family and can cause contagious diseases in sheep, goats, and wild ungulates. In the present study, two ORFV isolates (ORFV-SC isolated from Sichuan province and ORFV-SC1 produced by 60 passages of ORFV-SC in cells) were sequenced and compared to multiple ORFVs. The two ORFV sequences had entire genome sizes of 14,0707 bp and 141,154 bp, respectively, containing 130 and 131 genes, with a G + C content of 63% for the ORFV-SC sequence and 63.9% for the ORFV-SC1 sequence. Alignment of ORFV-SC and ORFV-SC1 with five other ORFV isolates revealed that ORFV-SC, ORFV-SC1, and NA1/11 shared > 95% nucleotide identity with 109 genes. Five genes (ORF007, ORF20, ORF080, ORF112, ORF116) have low amino acids identity between ORFV-SC and ORFV-SC1. Mutations in amino acids result in changes in the secondary and tertiary structure of ORF007, ORF020, and ORF112 proteins. The phylogenetic tree based on the complete genome sequence and 37 single genes revealed that the two ORFV isolates originated from sheep. Finally, animal experiments demonstrated that ORFV-SC1 is less harmful to rabbits than ORFV-SC. The exploration of two full-length viral genome sequences provides valuable information in ORFV biology and epidemiology research. Furthermore, ORFV-SC1 demonstrated an acceptable safety profile following animal vaccination, indicating its potential as a live ORFV vaccine.

Geological characteristics of shallow natural gas in eastern Sichuan and risk evaluation for tunneling: Chongqing–Wanzhou high-speed railway - Kunchen He; Peidong Su; Yougui Li; Youjun Ji; Haichuan Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Origin and accumulation of natural gas in the Ningbo Tectonic Zone in the Xihu Sag - Daxiang He; Youjun Tang; Rongfu Shi (Arabian Journal of Geosciences, 2021)

An analysis of potential investment returns of planted forests in South China - Pu Zhang; Youjun He; Yiming Feng; Rafael De La Torre; Hongyan Jia; Jixin Tang; Frederick Cubbage (New Forests, 2019)

Numerical simulation of the influence of aerosol radiation effect on urban boundary layer - Xinran Wang; Xiaodong He; Shiguang Miao; Youjun Dou (Science China Earth Sciences, 2018)

Improving the oral bioavailability of tapentadol via a carbamate prodrug approach: synthesis, bioactivation, and pharmacokinetics - Yingchao Li; Yongjun Wang; Ran Zhang; Cuiru Liu; Yue Wei; Jin Sun; Zhonggui He; Youjun Xu; Tianhong Zhang (Drug Delivery and Translational Research, 2018)

Molecular mechanisms underlying inhibition of STIM1-Orai1-mediated Ca2+ entry induced by 2-aminoethoxydiphenyl borate - Ming Wei; Yandong Zhou; Aomin Sun; Guolin Ma; Lian He; Lijuan Zhou; Shuce Zhang; Jin Liu; Shenyuan L. Zhang; Donald L. Gill; Youjun Wang (Pflügers Archiv - European Journal of Physiology, 2016)

Hugoniot and sound velocity of antigorite and evidence for sluggish decomposition - Youjun Zhang; Toshimori Sekine; Yin Yu; Hongliang He; Chuanmin Meng; Fusheng Liu; Mingjian Zhang (Physics and Chemistry of Minerals, 2014)